Family Factors and Their Relation to the Treatment Adherence of Pulmonary TB Patients in Surabaya - Dhian Satya Rachmawati; Dwi Priyantini; Qurrotul Aini (Universitas Airlangga, 2020)
Introduction: Pulmonary TB is a chronic disease of which is one of the keys to its successful management is the quality of the patient's family support system. The family has a role in the psychological wellbeing of sick family members in the care process. The purpose of this study was to look for the effects of family factors (family stress level and family resilience) with treatment adherence of pulmonary TB patients in North Surabaya.Methods: The design of this research was analytic observational research design with cross-sectional approach. A sample of 284 respondents was taken using proportional random sampling technique from 990 patients with pulmonary TB in the North Surabaya area. The instrument used was a questionnaire that had been tested for validity and reliability. Data were analyzed using Pearson correlation test at α ≤ 0.05.Results: The results showed that family stress level was mostly in the normal category (86.6%), family resilience was mostly in the good category (79.9%), and TB medication adherence was in the moderate category (39.8%). The Pearson correlation test results obtained family stress level associated with TB medication adherence (p = 0.004) and family resilience has a relationship with TB medication adherence (p = 0.001).Conclusion: Families can work to reduce stress and increase the resilience of their families to increase adherence with TB treatment in family members suffering from pulmonary TB